Development of Volleyball Smash Training Aid Media for FIK UNIMED Students - Abdur Rahman Daulian Hrp; Agung Sunarno; Amir Supriadi; Indrakasih Indrakasih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The main objective of this research is development of media for smash training aids as a volleyball learning media. This research was conducted at FIK State University of Medan in 2021. Research at FIK Unimed Medan will be carried out from February 9 to March 4, 2021. The type of research used is research development (Research and Development), a small trial sample of 6 students and a large trial of 10 students as well as media, sports and language experts. In small group trials of 3 lecturers, and large group trials of 3 lecturers, reaching 94.23% with valid criteria can be used. Sports experts of 92.5% with valid criteria can be used. The small group trial sample of 6 PKO FIK Unimed students reached 95.23% with very effective criteria, and a large group trial sample of 10 PKO FIK Unimed Medan students reaching 87.33% with a very effective rate. Then from the test of the effectiveness and efficiency of the smash aids it reached 98% with valid criteria for use and 96% with valid criteria for use. On the basis of the data obtained, the development of the Smash assistive media product was declared feasible to be developed as one of the learning media in game material volleyball.